Gastrocnemius activation deficits and running biomechanics after anterior cruciate ligament reconstruction: the missing link? - Forelli, Florian; Moiroux-Sahraoui, Ayrton; Mazeas, Jean; Pengue Koyi, Anais; Labib, Mouna; Cerrito, Adrien (Frontiers in Sports and Active Living, 2025)
BackgroundReturn to running (RTR) after anterior cruciate ligament reconstruction (ACL-R) remains challenging due to persistent neuromuscular deficits. This study examines gastrocnemius activation and running biomechanics in ACL-R patients.MethodsFifteen ACL-R patients and fifteen healthy controls were assessed using surface electromyography during isometric testing and treadmill running (10 km.h−1). Spatiotemporal parameters, including ground contact time, flight time, step width, cadence, stride length, and vertical stiffness, were analyzed.ResultsACL-R patients exhibited lower gastrocnemius activation during isometric testing (medial: 48.5% vs. 55.9% MVIC, p = 0.01; lateral: 42.1% vs. 47.5% MVIC, p = 0.03) and during running (medial: 45.2% vs. 53.1% MVIC, p < 0.01; lateral: 39.7% vs. 44.8% MVIC, p = 0.04). They also demonstrated altered running biomechanics, including longer ground contact time (0.29 vs. 0.26 s, p = 0.02, d = − 0.5), shorter stride length (1.32 vs. 1.41 m, p = 0.03, d = 0.9), reduced vertical stiffness (21.8 vs. 25.6 kN.m−1, p = 0.03, d = 0.5), and slightly increased step width (0.14 vs. 0.13 m, p = 0.05, d = 0.4). A significant negative correlation was observed between medial gastrocnemius activation during running and ground contact time (rs = −0.56, p = 0.02, ES = −0.6). Lateral gastrocnemius activation was positively correlated with stride length (rs = 0.49, p = 0.03, ES = 0.5), and medial gastrocnemius activation showed a moderate positive correlation with vertical stiffness (rs = 0.52, p = 0.04, ES = 0.5). Cadence did not show a statistically significant correlation with either medial or lateral gastrocnemius activation (rs = 0.36, p = 0.08, ES = 0.4 and rs = 0.45, p = 0.09, ES = 0.4, respectively).ConclusionGastrocnemius dysfunction persists after ACL-R, affecting running mechanics. These findings suggest that current rehabilitation protocols may need to incorporate plantar flexor training to optimize running mechanics post-ACL-R.